Solar water heating for universities and colleges: Meeting a need for cost-effective green technologies - Blakeway, David; Lowenthal, P.; Islam, S.; Murad, M.; Skorochod, P. (2013)
Copyright © (2013) by American Solar Energy Society.Educational institutions are showing interest in the application of Solar Water Heating (SWH) systems for dormitories and general HVAC as part of their strategy for reducing their carbon fuel consumption. Perennial Energy Consulting, Inc. (PEC) interviewed several educational institutions in the DC/MD/VA area over the past year concerning their efforts to demonstrate SWH and their plans for expanded implementation. There is an interest in installing SWH systems by some universities, but also unfamiliarity with the financial aspects of SWH system applications. PEC is developing a methodology to provide efficient ways of evaluating the costs of SWH and comparisons with sole reliance on electric and natural gas heating.